(3QSGdI aj edc GdYQH hcejJgs - (3jYbhH Hf ESMGb Hf GdUHGM GdcfOj, CHh jhSa,J (B260 (3g` s
(3ChdgG (B:s
(3CYGfjc Gddg Ydi bHhd GdMceI hCdgec CSJTYGQ GdadSaI SCdJ CcQec Gddg Cf CPcQ GdcdGe GdPi SeYJfi CNHQ Hg ef cJGH Gddg YR hLd ai Yde cejg edc GdYQH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B244s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B206 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B163 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi (B(3473(add)) s
Keywords: (3GdJGQjNs